2002
DOI: 10.5703/1288284313263
|View full text |Cite
|
Sign up to set email alerts
|

Load Tests on Pipe Piles for Development of CPT-Based Design Method

Abstract: Prepared in cooperation with the Indiana Department of Transportation and Federal Highway Administration. AbstractThis research focused on the drivability and load-carrying capacity of both open and closed-ended steel pipe piles. Two pipe piles (one open-ended, the other closed-ended) were installed in a sandy soil to the same depth. The site was extensively characterized. SPT and CPT tests were performed both before and after pile installation. A variety of soil indices and shear strength parameters (such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Kim et al 2002 found that it underpredicts significantly the load capacity of both closed-and open-ended piles for the conditions investigated by these authors. Regarding drivability, INDOT engineers have reported that predictions of the final driving depths and, thus, of the pile capacity made by design engineers are often unsatisfactory.…”
Section: Problem Statementmentioning
confidence: 68%
“…Kim et al 2002 found that it underpredicts significantly the load capacity of both closed-and open-ended piles for the conditions investigated by these authors. Regarding drivability, INDOT engineers have reported that predictions of the final driving depths and, thus, of the pile capacity made by design engineers are often unsatisfactory.…”
Section: Problem Statementmentioning
confidence: 68%